Aspek Pertanggungjawaban Notaris Dalam Perbuatan Melawan Hukum: Studi Kasus dan Implikasi Dalam Perjanjian Jual Beli - L, Leon; Gultom, Stevanus Redvin Novertua; Hasibuan, Muhamad Abdul Aziz; Zein, Muhammad Alif Raihan; Salsabilasyah, Firyal Nur; K, Karren; S, Surahmad (Media Hukum Indonesia (MHI), 2025)
A notary plays a crucial role in drafting authentic deeds as valid evidence in various agreements, including sale and purchase agreements. In carrying out their duties, notaries are bound by Law Number 2 of 2014 concerning Amendments to Law Number 30 of 2004 on the Notary Profession (UUJN). However, in practice, cases often arise where notaries are suspected of engaging in unlawful acts, either due to negligence or intentional misconduct, leading to legal disputes. One notable case highlighting the liability of notaries is District Court Decision Number 54/Pdt.G/2020/PN.Unr, which discusses the legal implications for notaries who commit violations in sale and purchase agreements. This case demonstrates that notaries may be held accountable under civil law and professional ethical codes if found guilty of legal violations. The involvement of notaries in unlawful acts can harm the parties involved in agreements and undermine public trust in the notarial profession. Therefore, concrete steps are needed to strengthen regulations, enhance supervision, and clarify sanctions for notaries who violate legal provisions to ensure the professionalism and integrity of notaries in every agreement they draft.